What About Worms!? - Willems, Mo; Higgins, Ryan T. (New York : Hyperion Books for Children, 2020)
Tiger unwittingly helps some worms overcome their fear of tigers with a well-placed, informative book, but will a wormy hug aid a fearful Tiger?
Keywords: Fear -- Juvenile fiction; Worry -- Juvenile fiction; Tiger -- Juvenile fiction; Worms -- Juvenile fiction; Gerald (Fictitious character : Willems) -- Juvenile fiction; Piggie (Fictitious character : Willems) -- Juvenile fiction; Fear -- Fiction; Worry -- Fiction; Tiger -- Fiction; Worms -- Fiction; Gerald (Fictitious character : Willems) -- Fiction; Piggie (Fictitious character : Willems) -- Fiction